Reconhecimento de línguas de sinais e educação de surdos no Brasil e na Suécia - Montes, Aline Lucia Baggio (2018)
The objective of this work is to investigate, in a comparative perspective, the documents that recognize sign languages in Brazil and Sweden and to analyze if their respective acknowledgments contributed to the educational process of the deaf in both countries. This is a documentary study, with content analysis as the main approach. In the midst of a broader discussion of linguistic rights and the right to use minority languages, advances in the education of deaf people - from a legal point of view - are beginning to be more explicit in the 1990s, marked by deaf and debates about the negative reflexes of the clinical-therapeutic model. The deaf community is then represented at the core of the political strategy of the multiculturalist movement, and studies on this aspect begin to strengthen in the international context, as well as discussions on the officialisation of sign languages. Sweden, the first country to give language status to a sign language, as well as the "Swedish model" of bilingual education, arouses great interest. The analysis lines were: type of recognition, analyzes of the texts of the Law Libras (nº 10.436 / 2002) and Law of the Swedish Language (SFS 2009: 600) and contributions of the documents for the education of the deaf. The methodology of comparative education studies showed important aspects. In Sweden, the right to acquire and use the Swedish language of signs as a mother tongue is provided for by law, and the country effectively contributes to the creation of real conditions for acquisition by the deaf community; linguistic policies govern the entire process of linguistic law and the right of language acquisition to the deaf. In Brazil, the right to purchase is not provided for by law and, thus, the paths to be covered by deaf children who seek acquisition of their language are not defined; the debates on Libras have always been closely linked to the debates on the rights of persons with disabilities, with the double categorization of the deaf being evident: persons with disabilities and members of minority groups. Therefore, the recognition of Libras did not guarantee the deaf people of Brazil the right to acquire sign language; and also did not promote the guarantee of a bilingual education. In Sweden, in view of the scenario studied, the law only reaffirmed the practice carried out over many years: sign language education throughout school age.